The role of ultrasound-guided perineural injection of the tibial nerve with a sub-anesthetic dosage of lidocaine for the diagnosis of tarsal tunnel syndrome - Iborra, Álvaro; Villanueva, Manuel; Barrett, Stephen L.; Vega-Zelaya, Lorena (Frontiers in Neurology, 2023)
Background Tarsal tunnel syndrome (TTS) involves entrapment of the tibial nerve at the medial ankle beneath the flexor retinaculum and its branches, the medial and lateral plantar nerves, as they course through the porta pedis formed by the deep fascia of the abductor hallucis muscle. TTS is likely underdiagnosed, because diagnosis is based on clinical evaluation and history of present illness. The ultrasound-guided lidocaine infiltration test (USLIT) is a simple approach that may aid in the diagnosis of TTS and predict the response to neurolysis of the tibial nerve and its branches. Traditional electrophysiological testing cannot confirm the diagnosis and only adds to other findings. Methods We performed a prospective study of 61 patients (23 men and 38 women) with a mean age of 51 (29–78) years who were diagnosed with idiopathic TTS using the ultrasound guided near-nerve needle sensory technique (USG-NNNS). Patients subsequently underwent USLIT of the tibial nerve to assess the effect on pain reduction and neurophysiological changes. Results USLIT led to an improvement in symptoms and nerve conduction velocity. The objective improvement in nerve conduction velocity can be used to document the pre-operative functional capacity of the nerve. USLIT may also be used as a possible quantitative indicator of whether the nerve has the potential to improve in neurophysiological terms and ultimately inform prognosis after surgical decompression. Conclusion USLIT is a simple technique with potential predictive value that can help the clinician to confirm the diagnosis of TTS before surgical decompression.